Preferences and Motivation of Tourists to Visit Turtle Ecotourism in Pariaman City - Ramadona, Ratu Insani; Budi Handoyo; Jurnal; Azmi Fitrisia; bin Suhadak, Saiful Adli (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Turtle ecotourism is one of the main attractions in Pariaman City which not only functions as a tourist attraction, but also as a means of education and conservation efforts. This study aims to analyze the preferences and motivations of tourists in visiting turtle ecotourism in Pariaman City. The research method uses a descriptive quantitative approach with data collection techniques through observation, questionnaires, and supporting interviews. The research sample was determined by random sampling of tourists who visited turtle conservation sites. The data was analyzed using SWOT analysis techniques for factor analysis to identify the main motivations for visits. The results of the study show that tourist preferences are dominated by interest in conservation educational activities, the experience of seeing turtles in person, and the natural atmosphere that is still natural. Meanwhile, it was found that tourists' high motivation for conservation education and the attractive experience of hatchling release are the main strength of turtle ecotourism in the city of Pariaman to develop. With aggressive strategy planning based on digital promotion, facility improvement, and educational collaboration, this destination has the potential to become a major ecotourism icon in West Sumatra.